Voltammetric study of 2-guanidinobenzimidazole: Electrode mechanism and determination at mercury electrode - Skrzypek, Sławomira; Mirceski, Valentin; Smarzewska, Sylwia; Guziejewski, Dariusz; Ciesielski, Witold (Institute of Organic Chemistry & Biochemistry, 2011)
Although 2-guanidinobenzimidazole (GBI; CAS: 5418-95-1) is a compound of biological interest, generally there is a lack of electrochemical studies and the methods of its determination. The GBI behavior at a mercury electrode was analyzed under conditions of linear sweep voltammetry (LSV), differential pulse voltammetry (DPV), square-wave voltammetry (SWV) and square-wave stripping voltammetry (SWSV). Although GBI is electrochemically inactive at mercury electrode it adsorbs at the mercury surface and catalyzes effectively the hydrogen evolution reaction. Theoretical analysis of two possible pathways, according to which the GBI electrode mechanism can be explained, is performed. Simple analysis of peak current and potential with respect to available time window, i.e. change of frequency can be helpful in discerning the character of the recorded SW current. The established electrode mechanism is assumed to involve a preceding chemical reaction in which the adsorbed catalyst (GBIads) is protonated and the protonated form of the catalyst (GBIH+(ads)) is irreversibly reduced at potential about –1.18 V vs Ag|AgCl (citrate buffer pH 2.5). New methods of voltammetric determination of 2-guanidinobenzimidazole were developed. The detection and quantifications limits were found to be 1 × 10–7, 1 × 10–6 mol l–1 (SWV); 8 × 10–8, 9 × 10–7 mol l–1 (SWSV); 4 × 10–7, 2 × 10–6 mol l–1 (DPV) and 6 × 10–7, 3 × 10–6 mol l–1 (LSV), respectively.